Health Impact of School Built Environment on Children - Ujjwala Chorasia; Sayalee Tendulkar; Keertana Gogia; Nitya Beerakayala; Kumar Sumit (Medsci Publications, 2023)
School-built environment impacts mental health, physical health, obesity, bullying, learning disorder, and respiratory disorders in children. The built environments of schools have a direct implication on the health of children. Indoor air quality in school buildings will play a role in children's exposure to pollution. One of the most consistently reported factors associated with children's active travel rates to school is the distance to school, with children more likely to walk or cycle to school the closer they live to the school. An evidence base regarding the built environment factors that shape decision-making and behavior related to active modes of travel in adults is emerging for policymakers. Functional aspects of the built environment include the distance between places; street design and geometry; street connectivity; path infrastructure, aesthetic qualities; safety; the mix of land uses; and the proximity and quality of destinations. Regarding architecture, the primary goal should be to create a space that maximizes natural light, airflow, and captivating aesthetics. Students spend their most important and developing years on school campuses; it is essential to consider their mental and physical health to create an environment where they can learn and develop their personalities in comfort. This paper discusses the health impacts that school-built environments have on children from a public health professional's perspective as well as an architect's viewpoint, as both institutions are crucial for children and adolescents to grow up in environments that encourage more active, safe, and sustainable lifestyles.